2019
DOI: 10.1002/phar.2311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Ticagrelor versus Prasugrel in Patients with Acute Coronary Syndrome: A Retrospective Cohort Analysis

Abstract: STUDY OBJECTIVE To compare the effectiveness and safety of ticagrelor versus prasugrel in preventing recurrent cardiovascular disease (CVD) and major bleeding events in patients with acute coronary syndrome (ACS). DESIGN Retrospective cohort analysis. DATA SOURCE Truven Commercial and Medicare Supplemental claims database (2011)(2012)(2013)(2014)(2015)(2016). PATIENTS Study consisted of adults with ACS who newly initiated ticagrelor or prasugrel within 7 days of their first ACS diagnosis and had no prior use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The observational literature evaluating outcomes of antiplatelet use in patients with ACS undergoing PCI has shown conflicting results 5–9,18,28 . Differences in how study designs address variability in follow‐up time, inclusion, and exclusion criteria, approaches for addressing covariates may lead to divergent conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observational literature evaluating outcomes of antiplatelet use in patients with ACS undergoing PCI has shown conflicting results 5–9,18,28 . Differences in how study designs address variability in follow‐up time, inclusion, and exclusion criteria, approaches for addressing covariates may lead to divergent conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Using a conventional ITT analytic approach that fails to address censoring events that are imbalanced between treatment groups, as well as differential censoring, can lead to different interpretations of the estimates. Dawwas et al evaluated the comparative effectiveness and safety of ticagrelor versus prasugrel in patients with ACS in a retrospective cohort analysis 28 . Their results indicated that ticagrelor was associated with a decreased risk of recurrent nonfatal cardiovascular events (HR: 0.80, 95% CI: 0.70–0.92) and major bleeding events (HR: 0.54, 95% CI: 0.41–0.70).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients, prasugrel and ticagrelor are preferred over clopidogrel due to improved cardiovascular outcomes [5]. The clinical superiority of prasugrel or ticagrelor above each other is debatable, as reports on this matter are not consistent [6][7][8][9][10][11]. The ISAR-REACT 5 trial, the only available randomized, clinical, head-to-head study, showed a reduction of composite ischemic endpoint (death, AMI, stroke) with prasugrel vs. ticagrelor in ACS patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study had limitations that impede interpretation of its results and applicability [10]. On the other hand, data from registries and observational studies are neutral [11] or show ischemic benefit when ticagrelor is used instead of prasugrel in patients with ACS or AMI [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation